Gold nanoparticles as antiangiogenic and antimetastatic agents. Issue 2 (February 2023) - Zamborlin, Agata; Voliani, Valerio
Graphical abstract: Highlights: Invasion and metastases are central features of cancer malignancy and constitute the primary cause of death for >90% of patients with cancer. The establishment of effective antiangiogenic/antimetastatic agents is the final frontier in cancer research. Strategies based on gold nanoparticles may provide disruptive advancements in oncology due to their peculiar optical properties coupled with the inertness and versatility. The potential application of gold nanoparticles to angiogenesis and metastasis is comprehensively reviewed. Abstract : Angiogenesis and metastasis are two interdependent cancer hallmarks, the latter of which is the key cause of treatment failure. Thus, establishing effective antiangiogenesis/antimetastasis agents is the final frontier in cancer research. Gold nanoparticles (GNPs) may provide disruptive advancements in this regard due to their intrinsic physical and physiological features. Here, we comprehensively discuss recent potential therapeutical strategies to treat angiogenesis and metastasis and present a critical review on the state-of-the-art in vitro and in vivo evaluations of the antiangiogenic/antimetastatic activity of GNPs. Finally, we provide perspectives on the contribution of GNPs to the advancement of cancer management.